Cerebellar integrity and contributions to cognition in C9orf72-mediated frontotemporal dementia. (April 2022) - Chen, Yu; Landin-Romero, Ramon; Kumfor, Fiona; Irish, Muireann; Dobson-Stone, Carol; Kwok, John B.; Halliday, Glenda M.; Hodges, John R.; Piguet, Olivier
Abstract: Background: The GGGGCC hexanucleotide repeat expansion in the non-coding region of the chromosome 9 open reading frame 72 gene ( C9orf72 ) is the most common genetic cause of familial frontotemporal dementia (FTD). This study aims to clarify the patterns of cerebellar atrophy in FTD patients with and without a C9orf72 repeat expansion compared with healthy controls and determine whether associations between cerebellar atrophy and cognition differ between patient groups. Methods: Thirty C9orf72 repeat expansion-positive FTD patients, 30 C9orf72 repeat expansion-negative FTD patients, and 30 age-, sex-, and education-matched healthy controls underwent brain MRI and cognitive assessments. Patient groups were matched for clinical diagnosis, disease duration, general cognition, and disease severity. Results: Compared with controls, the C9orf72 positive group showed cerebellar changes bilaterally involving the lobules V, VI, Crus I, Crus II, VIIb, VIIIa, left VIIIb, and right lobules I–IV. All these changes were localised within the regions affected in the C9orf72 negative group. No significant differences were found between patient groups. Correlation analyses with a liberal threshold found the cerebellar integrity to be associated with attention, language, and executive function in the C9orf72 positive group. In the C9orf72 negative group, these associations included attention, working memory, language, episodic memory, and executive function. Conclusions: This study clarifies the impact of C9orf72 repeat expansion on cerebellar integrity in FTD. The findings reveal overlapping patterns of cerebellar atrophy in C9orf72 positive and negative groups. The associations with cognitive functions suggest that the type of pathology linked with cerebellar atrophy is another relevant variable to consider in future studies.